Why derivatives on derivatives? The case of spread futures - Cuny, Charles J. (Journal of Financial Intermediation, 2006)
Recently, calendar spread futures, futures contracts whose underlying asset is the difference of two futures contracts with different delivery dates, have been successfully introduced for a number of financial futures contracts traded on the Chicago Board of Trade. A spread futures contract is not an obvious financial innovation, as it is a derivative on a derivative security: a spread futures position can be replicated by taking positions in the two underlying futures contracts, both of which may already be quite liquid. This paper provides a motivation for this innovation, demonstrating how the introduction of spread futures can, by changing the relative trading patterns of hedgers and informed traders, affect equilibrium bid–ask spreads, improve hedger welfare, and potentially improve market-maker expected profits. These results are robust both to allowing serial correlation of asset price changes, and investor preference for skewness.